Effects of Carbohydrate Mouth Rinsing on Cognition and Motor Skills in Sports Psychology - Dr. Lakshyashree,; Dr. Soumya Ranjan Lenka,; Dr. Priyanka Kumari Nahak,; Dr. Palak Gajjar,; Dr. Dushyant Bawiskar, (The Bioscan, 2026)
Background: Carbohydrate mouth rinsing (CMR) has gained attention as a practical strategy to enhance athletic performance without actual carbohydrate ingestion. While its role in endurance performance is well documented, its influence on cognitive functions and motor skills—critical components of sports performance—remains an evolving area of research. Objective: This review aims to examine the effects of carbohydrate mouth rinsing on cognitive performance (attention, decision-making, working memory) and motor skills (power, speed, coordination, endurance) within the context of sports psychology. It also explores the underlying neurological and psychological mechanisms influencing these outcomes. Method: A comprehensive literature search was conducted across databases including PubMed, Scopus, Web of Science, and SPORTDiscus. Studies included were peer-reviewed, written in English, involved human participants, and primarily used randomized controlled or crossover designs. A total of 322 records were identified, with 22 studies meeting the inclusion criteria after screening and eligibility assessment. Data were synthesized using a narrative approach due to heterogeneity in study designs and outcome measures. Results: Evidence suggests that carbohydrate mouth rinsing can positively influence both cognitive and motor performance. Improvements were observed in attention, reaction time, and decision-making, along with enhancements in power output, endurance, and motor coordination. These effects are largely attributed to the activation of oral carbohydrate receptors, which stimulate brain regions associated with reward, motor control, and effort regulation. Additionally, CMR appears to reduce perceived exertion and enhance motivation, contributing to improved performance outcomes. Conclusion: Carbohydrate mouth rinsing represents a simple, non-invasive strategy that may enhance athletic performance through central nervous system activation rather than metabolic pathways. Its benefits extend beyond physical performance to include cognitive and psychological domains. However, variability in protocols and study designs highlights the need for further research to standardize application and better understand individual responses. When used appropriately, CMR can serve as a valuable complementary tool in both training and competitive settings.